1992
DOI: 10.1161/01.hyp.20.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin dependence of endothelium-mediated renal hemodynamics.

Abstract: Endothelium-derived relaxing factor has been shown to regulate renal blood flow, and inhibition of its synthesis increases blood pressure and renal vascular resistance and decreases renal blood flow. Using the substrate antagonist A^-nitro-L-arginine methyl ester (L-NAME), we tested whether renal vasoconstriction induced by endothelium-derived relaxing factor synthesis inhibition could be mediated in part by angiotensin II. In 14 control rats, 10 mg/kg body wt L-NAME increased blood pressure from 106±6 to 126±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 29 publications
1
41
1
Order By: Relevance
“…We have previously reported that in anesthetized normotensive rats, acute blockade of Ang II largely diminished the increase in renal vascular resistance seen with EDNO synthesis inhibition, 14 ' 15 suggesting that local EDNO production balances the renal vasoconstrictor effect of Ang II and thereby maintains renal blood flow. Based on these observations, we hypothesized that in 2K1C hypertension with elevated Ang II but only mild renal artery stenosis, EDNO should have a greater influence on regional blood flow compared with normotensive controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously reported that in anesthetized normotensive rats, acute blockade of Ang II largely diminished the increase in renal vascular resistance seen with EDNO synthesis inhibition, 14 ' 15 suggesting that local EDNO production balances the renal vasoconstrictor effect of Ang II and thereby maintains renal blood flow. Based on these observations, we hypothesized that in 2K1C hypertension with elevated Ang II but only mild renal artery stenosis, EDNO should have a greater influence on regional blood flow compared with normotensive controls.…”
Section: Discussionmentioning
confidence: 97%
“…7 In various models of hypertension, including two-kidney, one clip (2K1C) Goldblatt, 1 aortic coarctation, 14 Dahl salt-sensitive, 3 and deoxycorticosterone acetate-salt 1 hypertension as well as in genetically spontaneously hypertensive rats, 2 endothelium-dependent vascular relaxation in vitro is impaired but may be restored by reversing the hypertension. 1 These observations suggest that endothelial dysfunction associated with hypertension may be due to insufficient production of the intrinsic vasodilator endothelium-derived nitric oxide (EDNO).…”
mentioning
confidence: 99%
“…We then inhibited NOS because we have found that, in anesthetized rats 18 and mice, 14 the decrease in RBF after L-NAME was dependent on the renin-angiotensin system. We did observe that the renal vasoconstrictor response in Sv-129 was significantly greater than in C-57, despite their lower PRC.…”
Section: Discussionmentioning
confidence: 99%
“…First, we compared the pressor and renal vasoconstrictor response to a 10-mg/kg bw blocking dose of L-NAME 12,18 in the two strains. Additionally, changes in RBF in response to sequential decreases in renal perfusion pressure were monitored using an adjustable aortic constrictor as previously described.…”
Section: Response To Reduced Renal Perfusion Pressure and Nos Inhibitionmentioning
confidence: 99%
“…The physiologic results on sodium and water reabsorption and renal hemodynamic may have been aggravated in AT 2 Ϫ/Ϫ mice by the deletion of the AT 2 receptor and the upregulation of the AT 1 receptor. In rats, AT 1 receptor blockade reduced or abolished the renal vasoconstriction after L-NAME treatment (28,29). The AT 2 receptor mediates vasodilation and sodium excretion and opposes the effects of AT 1 receptor stimulation.…”
Section: Discussionmentioning
confidence: 99%